Manual DALK in Keratoconus: An Ex Vivo Light and Transmission Electron Microscopy Analysis 2 Years After Surgery. Issue 3 (27th March 2022) - Favuzza, Eleonora; Mencucci, Rita; Rosa, Irene; Cennamo, Michela; Manetti, Mirko; Marini, Mirca
Abstract : Purpose: The aim of this study was to evaluate the microscopic structure of a human cornea 2 years after manual deep anterior lamellar keratoplasty (DALK) for keratoconus with a recipient residual stromal bed thickness of 100 μm, using light and transmission electron microscopy. Methods: A human cornea treated with manual DALK for keratoconus 2 years before was removed during penetrating keratoplasty because of stromal opacity of unknown origin, involving about half of the sample. The transparent half of the specimen was processed for light and transmission electron microscopy. Results: Light microscopy examination performed with different staining techniques (hematoxylin and eosin, Picrosirius red, and Masson trichrome) revealed a homogeneous stroma. No interface was detected. Electron microscopy confirmed these findings. Conclusions: This study confirmed the available clinical and confocal studies that show progressive stromal remodeling after manual DALK. Two years after surgery, no posterior stromal interface was detected.